Efektivitas dan Efisiensi Produksi Sorgum (Sorghum bicolor (L.) Moench) sebagai Hijauan Berkualitas Tinggi: Effectivity and Efficiency Evaluation of Sorghum (Sorghum bicolor (L.) Moench) Production as a High Forage Quality - Satria Mulyadi Putra, Erlangga; Nur Rochmah Kumalasari; Luki Abdullah (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2025)
Sorghum (Sorghum bicolor L. Moench) has the potential as a high-nutritional forage for livestock and can withstand drought conditions. This research aimed to analyze the effectivity and efficiency of each stage in the sorghum production process. The research was conducted from 2023 to 2024 at the Jonggol Animal Science Teaching and Research Unit (JASTRU). An exploratory and observational approach was established following with the snowball-sampling method and Data Envelopment Analysis (DEA) with a Variable Return to Scale (VRS) model as an analysis tool. The research indicated that March had the highest effectivity value in achieving the sorghum production target, with an efficiency score of one (optimum) at each stage of sorghum production. However, improvements were necessary in land preparation, planting, maintenance, and harvesting sorghum forage in other months. Environmental factors were influencing sorghum production that contributed to the highest increase in March. The sorghum production process in March could establish as a standard for maximizing productivity in the next cycle or ratoon. The research concluded that sorghum reached the best results in March, with the highest production effectivity and an optimum efficiency value at every stage of production in the private company. Key words: DEA analysis, effectivity, efficiency, production, sorghum